The MEQUAL scale: measure of service quality in management education. Issue 4 (13th November 2017) - Verma, Sanjeev; Prasad, Ram Komal
Abstract : Purpose: The purpose of this paper is to develop an empirically validated scale to measure the students' perception of service quality in management education. Design/methodology/approach: In this study, a three-stage systematic procedure of scale development has been adopted. Initially, extant literature review delineated the construct. Exploratory study techniques like focus group study and expert opinion helped in purifying the scale. In the second stage, principal component analysis with varimax rotation and Kaiser normalization (exploratory factor analysis) was used to refine the scale. Finally, multi-trait-multimethod matrix analysis was done to test the reliability and validity of the scale. Findings: A 25-item multi-dimensional construct with six factors (academic aspect, professional assurance, behavioral responses and supports, industry institute interaction, non-academic aspects and physical support) was derived scientifically for measuring service quality in management education. Psychometrically, the scale exhibits internal consistency and remains consistent across the samples. The scale passes the requisite reliability and validity tests (construct, convergent, discriminant, nomological, predictive) with all values within limits. Practical implications: Scientific and structured multi-dimensional construct for service quality in management education will help academicians, administrators and regulators in designing a process-oriented system for enhanced student satisfaction and performance. Originality/value: This study is an incremental attempt to develop an empirically validated scale for measuring the service quality level and resultant satisfaction in management education.